Emotional intelligence and its relationship to satisfaction with life (Journal of Hama University, 2021)
The study aimed to uncover the relationship between emotional intelligence and its relationship with life satisfaction in a sample of first-year students at the Faculty of Science at Damascus University, as well as to identify differences in emotional intelligence and life satisfaction according to (gender) variables. The research sample reached (220) students And one of them (75 males, 145 females). The research was applied in the first semester of the 2019-2020 academic year. The study tools consisted of: the emotional intelligence scale prepared by Adam Ibrahim Hassan Mahmoud (2017) and the life satisfaction scale by Magdy El Desouki (1998)). The results of the study showed the following: that the level of emotional intelligence of the members of the research sample was of a moderate degree, and the level of life satisfaction was also moderate. The results of the hypotheses showed: There is no significant association between emotional intelligence and life satisfaction among the members of the research sample the absence of significant differences in emotional intelligence among the sample members due to the variable (gender), and the absence of significant differences in life satisfaction among the sample members attributable to Variable (gender).